Pandemic H1N1 influenza surveillance in Haiti, July–December 2009. Issue 5 (30th November 2012) - Fitter, David L.; Freeman, Nicole M.; Buteau, Josiane; Magloire, Roc; Sessions, Wendy M.; Guo, Lizheng; Katz, Mark A.; Boncy, Jacques
<x xml:space="preserve">Abstract</x> Please cite this paper as: Fitter et al. (2012) Pandemic H1N1 influenza surveillance in Haiti, July–December 2009. Influenza and Other Respiratory Viruses DOI: 10.1111/irv.12060. From June 2009 through December 2009, Haiti conducted sentinel surveillance for influenza. 499 samples were collected and tested using real‐time RT‐PCR. 197 (39.5%) were positive for influenza, including 95 (48%) pandemic (H1N1) 2009, 57 (29%) seasonal influenza A and 45 (23%) influenza B. The median age of pandemic (H1N1) 2009 cases was 21.7; two‐thirds of pandemic (H1N1) 2009 cases were in patients aged 6 years – 35 years. Pandemic activity peaked in September and co‐circulated with other influenza subtypes. The age distribution and seasonality of pandemic (H1N1) 2009 in Haiti were similar to other countries in the Caribbean region.